Green Synthesis of Thiazolidine-2,4-dione Derivatives and Their Lipoxygenase Inhibition Activity With QSAR and Molecular Docking Studies - Lončarić, Melita; Strelec, Ivica; Pavić, Valentina; Rastija, Vesna; Karnaš, Maja; Molnar, Maja (Frontiers in Chemistry, 2022)
Thiazolidinediones are five-membered, heterocyclic compounds that possess a number of pharmacological activities such as antihyperglycemic, antitumor, antiarthritic, anti-inflammatory and antimicrobial. Conventional methods for their synthesis are often environmentally unacceptable due to utilization of various catalysts and organic solvents. In this study, deep eutectic solvents were used in the synthesis of thiazolidinedione derivatives that acted both as solvents and catalysts. Initially, a screening of 20 choline chloride based deep eutectic solvents for thiazolidinedione synthesis, via Knoevenagel condensation, was performed in order to find the most suitable solvent. Deep eutectic solvent, choline chloride: N-methylurea, was proven to be the best for further synthesis of 19 thiazolidinedione derivatives. Synthesized thiazolidinediones are obtained in yields from 21.49 % to 90.90 %. The synthesized compounds were tested for inhibition of lipid peroxidation as well as for inhibition of soy lipoxygenase enzyme activity. The antioxidant activity of the compounds was also determined by the ABTS and DPPH method. Compounds showed lipoxygenase inhibition in the range from 7.7 % to 76.3 %. QSAR model (R2 = 0.88; Q2loo = 0.77; F = 33.69) for the inhibition of soybean lipoxygenase was obtained with descriptors Mor29m, G2u, and MAXDP. The molecular docking confirms experimentally obtained results finding the binding affinity and interactions with the active sites of soybean LOX-3.